Perceived stress and its determinants among postmenopausal women in Urban Puducherry - Gokul Sarveswaran; Venkatachalam Jayaseelan; Yuvaraj Krishnamoorthy; Manikandanesan Sakthivel; Yashodha Arivarasan; Karthiga Vijayakumar; Yamini Marimuthu (Wolters Kluwer Medknow Publications, 2021)
Background: Menopause characterized by a gradual decline in ovarian hormones takes its toll on the women both physically and mentally. These health problems can negatively impact the mental status. Hence, the current study was done to determine the level of stress and its associated factors among postmenopausal women in urban Puducherry, India. Materials and Methods: A facility-based cross-sectional study was done among 219 postmenopausal women attending the outpatient department in urban primary health center during May 2017-June 2017. Information regarding sociodemographic profile was collected using pretested semi-structured questionnaire and Cohen's Perceived Stress Scale was used to assess the stress level. We calculated adjusted prevalence ratios (aPRs) to identify the determinants of stress. Results: Among 219 participants, 46.6% were in the age group of 60-74 years; 32.9% had primary to secondary level of education; 56.2% were unemployed; 42.5% belonged to lower socioeconomic class; and 32.9% had both diabetes mellitus and hypertension. The prevalence of stress among the postmenopausal women was 26.0% (95% confidence interval: 20.7-32.2). Postmenopausal woman with higher education (aPR - 2.18), belonging to nuclear family (aPR - 1.93), lesser parity (aPR - 1.18), and current alcohol/tobacco users (aPR-2.32) were found to have a significant association with stress among the study participants. Conclusion: The current study showed that more than one-fourth of the postmenopausal women had high to very high level of stress. Education, religion, parity, and substance abuse were the significant determinants of stress. However, further longitudinal research needs to be done to determine whether the factors informed in the current study are truly associated with stress and develop interventions accordingly.